Weight awareness among parents and health care providers in Sharjah, UAE - Abdelreheim, Naguib M.; Ramadan Ali, Nehad G.; Vamegh, Motahareh H.; Dejan, Efaf A.; Swilem, Mamdouh; Ahmed, Manzoor (International Journal of Research in Medical Sciences, 2017)
Background: This study looks at weight perception among parents and health care providers in Sharjah, UAE. Methods: This study was done through reviewing 1000 patients files who visited the paediatric OPD in university hospital Sharjah (UHS) during 2015. The files were reviewed for the cause of the visit, the diagnosis of weight status and weight counselling. Results: 18% of study patients were either overweight or obese. In children with abnormal weight status, the cause of the visits was weight related in 3.3% of patients, while it was due to weight unrelated causes in 96.7%. Weight counselling in obese individuals were reported in 35.5% of obese patients. While in overweight group, weight counselling was found in 5% of the patients and in patients with normal BMI, counselling was done in 0.2% of patients. Conclusions: This study shows clear defects in weight awareness and perception in parents and health care providers. Most parents are either not aware about the weight status of their kids or they don’t consider overweight or obesity as medical issues that require medical advice. The very low percentage of specific weight counselling shows weight counselling is not practiced if these patients are evaluated for other complaints. Weight misperception among parents and health care providers can be genuine barriers for prevention of childhood obesity.